Genetics of the signs of rice clusters - V. A. Dzyuba; L. V. Esaulova; I. N. Chukhir; T. L. Korotenko; A. G. Zelensky (Зерновое хозяйство России, 2019)
From the literature, more than 1000 active rice genes are known, from which chromosomal and genetic maps are drawn. Some of them have specific localization in the gene linkage groups. Knowing the specific gene localization in the chromosome, their interaction, interrelations with other neighboring alleles, it is possible to select the parental pairs to hybridize the models of new genotypes and varieties with the necessary traits. The botanical concept of a rice cluster includes all the quantitative and qualitative characteristics of the panicle. The scientific literature describes more than 20 signs that characterize a panicle. At the same time, panicle signs are divided into cluster and spikelet factors (grains). The article presents the characteristics of the parental individuals and the F1 and F3 hybrids of rice, the results of the hybridological analysis, the description of the genes and their manifestation in the hybrid combinations. We recommend using valuable genotypes in the selection of parental pairs for hybridization in the process of developing new varieties. In the genetic formulas of varieties and hybrids, each trait is represented by one symbol, as it is in the diploid state. The dominant genes are designated by uppercase (capital) symbols, the recessive one are written by lowercase letters. There have been determined the values of the dominance coefficients, which indicate the trait inheritance in F1. The most traits show the effect of dominance and overdominance, which indicates the possibility of their use in the breeding process when developing the source material and new rice varieties. There was carried out a hybridological analysis, which showed the digenic type of inheritance.